2016
DOI: 10.31234/osf.io/7ukmr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Severity and susceptibility: measuring the perceived effectiveness and believability of tobacco health warnings

Abstract: Background: Pictorial tobacco health warning labels (HWLs) have been shown to be more effective than text-only HWLs in changing smoking attitudes and intentions. However, there is contradictory evidence regarding how the severity of the content of HWLs influences responses to them. Methods: We examined the perceived believability and effectiveness of HWLs in an online study using a convenience sample of non-smokers (N = 437) and smokers (N = 436). HWLs were in one of three formats: (text-only, a moderately sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…We found that highly-severe warnings increase self-reported avoidance, reactance and motivation to quit smoking compared to moderately-severe warnings. This finding supports our previous online study using the same warnings, which found that the highly-severe warnings were perceived as more effective and believable by both non-smokers and current smokers (48).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found that highly-severe warnings increase self-reported avoidance, reactance and motivation to quit smoking compared to moderately-severe warnings. This finding supports our previous online study using the same warnings, which found that the highly-severe warnings were perceived as more effective and believable by both non-smokers and current smokers (48).…”
Section: Discussionsupporting
confidence: 90%
“…We next examined the extent to which these loss-framed messages focusing on the long-term consequences of smoking should be severe. Previous research has found that highly-severe warnings increase intentions to quit (42) are rated as more believable and effective (43) and increase perceived effectiveness of the warnings to discourage smoking (44).…”
Section: Warning Severitymentioning
confidence: 99%
“…With regard to image‐and‐text HWLs, uncertainty also remains around the types of images that may exert the greatest effect. Warnings including shocking or explicit pictures are most likely to be believed and are rated as more effective than those with less severe pictures [29]. The former, however, may also increase reactance and avoidance behaviours [28] and may be less acceptable [30].…”
Section: Introductionmentioning
confidence: 99%
“…We suggest this may be due to the pictorial used, with the pancreatic cancer warning displaying a close-up of a yellow eye, which is arguably novel and memorable, while the anxiety warning depicted a man pulling at his hair. Previous research has suggested that more ‘severe’ or grotesque warnings increase smokers’ intentions to quit and are rated as more believable and effective than less severe warnings 21 22…”
Section: Discussionmentioning
confidence: 99%